(untitled) (CIPEEX, 2023)
This work explored the relevance of the “Brazilian Solar Belt” as a means of improving energy efficiency and reducing the carbon footprint in Anápolis, Goiás. Brazil, with its vast territorial extension and high incidence of solar radiation, has significant potential for the transition to a more sustainable energy matrix. The “Brazilian Sun Belt” was identified by the National Institute for Space Research (INPE) as a region with high levels of solar irradiation, stretching from the Northeast to the Pantanal. Anápolis, located in this solar belt, is emerging as a center with great potential for photovoltaic energy generation. The study analyzed Anápolis’ current energy infrastructure and the specific energy challenges the city faces, including growing demand and the need to reduce greenhouse gas emissions. The city receives significant levels of solar irradiation, making it ideal for photovoltaic projects. In conclusion, Anápolis exemplifies the challenges and opportunities facing Brazil in the search for a cleaner and more sustainable energy matrix. With the adoption of renewable energies such as solar, Anápolis and other cities in the “Brazilian Solar Belt” have the potential to lead the country towards a more sustainable future, where economic growth is aligned with environmental preservation and energy resilience.